VD_FINDINFO HC / 2009 / 32 vom 20. März 2009 - VD Tribunal cantonal (2009)
DIVORCE, OBLIGATION D'ENTRETIEN, ACTION EN MODIFICATION | 129 al. 1 CC, 138 al. 1 CC, 145 al. 1 CC, 451 ch. 3 CPC, 452 al. 2 CPC, 471 al. 3 CPC